Conceptual design of the natural fiber composites of car spoiler using hybrid method - Sayed Idros, Syed Muhammad Ayyub (2022)
This study presents the natural fiber composite filament as an environmentally friendly material for the car spoiler and a conceptual design of car spoiler in a stage of product development process for natural fiber composites. The objective of this study is to analyze the mechanical properties and the material setting of natural fiber composite using Fused Deposition Modelling (FDM). Next, to determine the best design concept of the generated car spoiler and to determine the best material of natural fiber composite for the best design of car spoiler using hybrid method. Four natural fiber composite filaments were used in the Fused Deposition Modelling (FDM) process to obtain the printing setting. The tensile and flexural testing were done to obtain the mechanical properties of the natural fiber composite filament. Subsequently, five design concepts were generated by using morphological chart and biomimetic method. Finite element analysis (FEA) was used then to analyze the ir performance using Solidworks software. Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method was_ used as the decision-making too ls. As a results, the mechanical properties from the testing for PLA composite filaments shows PLA + Metal has the highest value with 53 .65 MPa for tensile strength, 6261.77 MPa for young mod ulus, 70.23 MPa for flexural strength, and 2714.267 MPa for flexural mod ulus. Next, the design concept 5 with the infill pattern of rib + I, were the best compared to others because of the lowest value of Von Mises Stress and displacement in finite element analysis with the value of 2.1 14 MPa and 1 .123 MPa respectively. TOPSIS method shows that PLA + Metal was the best PLA composite filament for the best design concept of car spoiler with first ran king in performance score. This study shows that the Morphological Chart and TOPSIS method can helps engineers and researchers in developing design concept that inspired by nature, as well as the best design concept and the best material selection using the systematic strategy.